The aging intellect - Powell, Douglas H. (Routledge, 2011)
"The Aging Intellect is written for the large number of professionals, including social workers, nurses, retirement home administrators, doctors, psychologists, pastors and others, who oversee the well being of elderly women and men. It provides elder care workers with an array of suggestions (beyond exercising and eating right) that can improve, maintain or maximize the quality of their client's mental abilities for as long as possible. The Aging Intellect serves its purpose by addressing four major issues associated with age-related cognitive decline, each of which has a solid research footing and is within the reach of most seniors"